Anaerobic biological treatment of wastewater from paper recycling industry by UASB reactor - Iftikhar, Aaima; Hayat, Malik Tahir; Zeb, Bibi Saima; Maria, Maria Siddique; Bhatti, Zulfiqar Ahmed; Abbasi, Umara; Mahmood, Qaisar (Universiti Kebangsaan Malaysia, 2023)
The use of an upflow anaerobic sludge blanket (UASB) reactor for the treatment of paper recycling industry effluent containing different pollutants was investigated. In the first phase, reactor was fed with anaerobic sludge and in the second phase, synthetic influent solution with different macro-nutrients and micro-nutrients, trace elements as well as glucose were added as a basis of food and energy. In order to enhance sludge granulation and increase the growth, anaerobic bacterial biomass culture was added and operated for one month. Samples from paper recycling industry effluent with different dilutions were analyzed at a hydraulic retention time (HRT) of 24 h and at 37 °C mesophilic temperature. The removal efficiencies of chemical oxygen demand (COD), biological oxygen demand (BOD), electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), total solids (TS), nitrates, phosphates, heavy metals (Hg, Pb, Cd, Cr, Cu) and pH were upto 87%, 93%, 77%, 79%, 88%, 82%, 92%, 94%, 86%, 91%, 93%, 98%, 98%, and 7.21 with different of wastewater concentration/percent dilutions 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, 10:0 wastewater. This study concluded that UASB technique was a suitable choice for treating different pollutants in paper recycling industry wastewater.